Evaluating the Fulfillment of Health Rights for Persons with Disabilities in Jakarta’s Community Health Centers - Liany, Lusy; Purwaningsih, Endang; Basrowi, Basrowi; Queroda, Phillip G; Iskandar, Farhan Putra (Jurnal Pembangunan Hukum Indonesia, 2025)
Access to equitable health services is a priority in guaranteeing human rights, especially for persons with disabilities, which is implemented in the primary health service systems of developing countries. Although there is a comprehensive legal framework, structural and institutional barriers are essential in the fulfillment of inclusive health services. This study provides an analysis of the obstacles and implementation of the fulfillment of health rights of persons with disabilities at the Jatinegara Kaum Health Center. Puskesmas are at the forefront of providing health services, in line with the goals of Law Number 8 of 2016. The Jatinegara Kaum Health Center is the object of research because there is the highest population of people with disabilities in DKI Jakarta. The research was conducted by combining a legal framework with empirical data in the form of interviews, field observations, and document analysis, to evaluate systemic health service delivery practices. This study found a gap in the fulfillment of health rights with positive legal regulations that apply. Obstacles include limited infrastructure, limited medicines, supporting equipment, and lack of competence of medical personnel and the involvement of families of people with disabilities. This research provides recommendations for improving inclusive health facilities, the competence of health workers through special training, maximum allocation of funds, and cross-sectoral collaboration, in order to fulfill the health rights of persons with disabilities in a comprehensive and comprehensive manner.